PENGARUH SISTEM PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI PADA UKM DI SURAKARTA) - Killa Kusuma; Rosita (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
Currently, SMEs are the main pillar of the economy in Indonesia, but the large number of SMEs in Indonesia cannot be separated from existing difficulties, including accounting fraud. This study aims to determine the impact of the effectiveness of internal control, compliance with accounting rules, suitability of compensation to the tendency of accounting fraud by using a population of 25 Culinary SMEs in Surakarta City with 125 employees as respondents. This research is a type of quantitative research. The sampling method used is purposive sampling technique. The questionnaire was chosen as a data collection technique. This study uses quantitative analysis with validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, coefficient of determination, F test, and t test using the IBM SPSS version 19 assistance program. has a negative effect on the tendency of accounting fraud, while the suitability of compensation has a no effect on the tendency of accounting fraud